Applications of modelling to the improvement of sports technique - Yeadon, M. R. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Models of high jumping, high bar circling, swinging on rings, tumbling, diving, twisting and balancing can give insight into the mechanics of these movements and provide a basis for coaching in order to improve performance. Such models can also be used to investigate the viability of new movements or new techniques. Training aids based on models of sports movements have the potential to speed learning and enable athletes to reach new levels of achievement.